Federalism and development planning in Nigeria : Conference on National Reconstruction and Development in Nigeria, March 24-29, 1969 - Adedeji, Adebayo (Ile-Ife, Nigeria: Institute of Public Administration, 1969)
The paper appraises Nigeria's experience in development planning and plan implementation against the background of the federal nature of its system government.
oif 11/04/2019
Nigeriana
Keywords: Economic development; Federalism; Nigeria